Needlework, affect and social transformation : the everyday textures of feminist activism - May, Katja (London ; New York : Bloomsbury Visual Arts, 2023)
"Needlework, Affect and Social Transformation offers an original framework for moving beyond binary discourses that class practices of needlework as either feminist or reactionary. Using transnational, contemporary case studies - such as the Social Justice Sewing Academy, fictionalised Bangladeshi garment workers as well as the famous Pussyhat Project - Katja May suggests a new approach to the interpretation of textile crafts as an affective social practice, and draws on under-represented issues of race. May connects her study to broader material and social conditions of inequality, allowing for a nuanced and sensitive understanding of the role of needlework in feminist political activism. This broader look at how textile crafts function in the realms of politics and activism conceptualizes quilting, dressmaking, embroidery and knitting as routine activities invested with emotions and entangled with material and social conditions as well as political potential"--
Introduction: The Affective Politics of Needlework -- 1. Quilting Black Resistance: Slavery's Afterlives, Creativity and Social Justice -- 2. Sewing Desire: Homework, Gendered Agency and Bangladeshi Diaspora -- 3. Stitching Transnational Solidarity: Textile Crafts and Cross-Cultural Encounters -- 4. Knitting Feminist Politics: Craftivism and Affective Tension -- Coda: Un-making Whiteness -- Appendix.
Includes bibliographical references and index.
Keywords: Craftivism; Craftivism; Needlework -- Political aspects; Needlework -- Social aspects; Textile crafts -- Political aspects; Textile crafts -- Social aspects